Estructura conceptual de la competencia afrontamiento en estudiantes de Licenciatura en Enfermería - Jaqueline Garcia Rodriguez; Silvia Colunga Santos; Soledad Yanedy García Peláez (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
The characteristics of the healthcare contexts and the praxis of the Nursing professionals justify emotional education. However, in Cuba, the training of these professionals emphasizes the acquisition of skills and abilities with little reference to formation of socio-emotional competencies. These competencies are divided into five groups that contain others of lesser generality. Included in emotional regulation is coping, considered an initial step for self-confidence, managing the uncertainty, adaptation to changes and resilience. The work describes conceptually the competence coping, with the purpose of contributing to their greater understanding and encourage their training in the context of medical higher education. Three procedural axes are proposed, their indicators in terms of desirable performance and required evidence.